+0  
 
0
393
1
avatar

6x/x+4 + 4 = 2x-2/x-1

Guest May 14, 2017
 #1
avatar+93664 
+2

 

6x/x+4 + 4 = 2x-2/x-1

 

Do you mean     

6x/(x+4) + 4 = (2x-2)/(x-1)     ?

 

\(\frac{6x}{(x+4)} + 4 = \frac{(2x-2)}{(x-1)}\\     LCD=(x+4)(x-1)\\ (x+4)(x-1)[\frac{6x}{(x+4)} + 4 ]=(x+4)(x-1)[ \frac{(2x-2)}{(x-1)}]\\     \frac{6x(x+4)(x-1)}{(x+4)} + 4 (x+4)(x-1)= \frac{(2x-2)(x+4)(x-1)}{(x-1)}\\     6x(x-1)+ 4 (x+4)(x-1)=(2x-2)(x+4)\\ 6x^2-6x+ 4 (x^2+3x-4)=2x^2+6x-8\\ 6x^2-6x+ 4x^2+12x-16=2x^2+6x-8\\ 8x^2-8=0\\ x^2-1=0\\ (x-1)(x+1)=0\\ x=\pm1 \)

 

Edit:

x cannot equal 1 becasue it would make the denominator in the question = 0 

so the answer is 

x = -1

Thanks for pointing this out to me CPhill   wink

I should have noted at the very beginning that x cannot equal  1 or -4 !!

Mistakes like this need to be carefully guarded against !!

Melody  May 15, 2017
edited by Melody  May 15, 2017

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.